Co-creation in a digital health living lab: A case study - Fotis, Theofanis; Kioskli, Kitty; Sundaralingam, Anand; Fasihi, Amer; Mouratidis, Haralambos (Frontiers in Public Health, 2023)
Co-creation in healthcare and especially in developing digital health solutions has been widely identified as a fundamental principle for person-centred technologies that could accelerate the adaptation of innovation. A digital health living lab based in the community offers a sustainable and real-life environment to ideate, develop and evaluate digital health solutions addressing the needs of multiple stakeholders. This paper presents the experience of the School of Sport & Health Sciences at the University of Brighton in establishing a Digital health Living Lab. In addition, we share a proposed step by step approach in establishing such a living lab in the community supplemented by a case study of product development.